The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1155/2019/8690906
|View full text |Cite
|
Sign up to set email alerts
|

Regular Analysis of Aero-Diesel Piston Engine between Combustion Chamber Size and Emission

Abstract: The emission of aero-engines has been a focused issue, studying the regular of combustion chamber size on engine emission performance, with an aviation diesel piston engine as the object of study; the numerical model of diesel combustion spray and emission model are analyzed; and the dynamics grid of the combustion chamber is meshed by FIRE software, analyzing the relationship between the reentrant diameter, the maximum depth of the combustion chamber, and the emission generation, comparing the NOx and soot em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Xue M established the simulation model of in-cylinder combustion of piston aviation and verified by experiments, which state that the combustion center of gravity will increase by increasing the ignition advance angle [23]. Pan Z J et al analyzed the impact of combustion chamber diameter and depth on emissions, which showed that properly reducing combustion chamber diameter and diameter-depth ratio can reduce emissions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Xue M established the simulation model of in-cylinder combustion of piston aviation and verified by experiments, which state that the combustion center of gravity will increase by increasing the ignition advance angle [23]. Pan Z J et al analyzed the impact of combustion chamber diameter and depth on emissions, which showed that properly reducing combustion chamber diameter and diameter-depth ratio can reduce emissions [24].…”
Section: Introductionmentioning
confidence: 99%
“…In the design process of aviation heavy fuel piston engine, under the influence of compression ignition mode and under high cylinder pressure, the engine block needs to overcome the explosion pressure and high temperature generated during engine operation, and the body needs good strength and stiffness to ensure the safety and reliability of the engine (Pan and He, 2015). At present, the conventional method to enhance the engine block stiffness is to enhance the body wall thickness or replace high-strength materials, but replacing the lightweight high-performance materials will increase the cost of the engine (Pan and Guo, 2019; Pan et al , 2019), usually choose to increase the thickness or use cast iron materials to improve the stiffness. As the engine needs to carry the aircraft to fly off the ground, reducing the weight of the engine can reduce the weight of the aircraft.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the military's single standard on fuel and the economy and availability for civil use, the compression ignition aviation piston engine has become a hot research topic [1]. Compared with jet engines, compression ignition piston-propeller aircraft has better fuel economy [2], low noise [3], emission, and easy maintenance. The unmanned aerial vehicle (UAV) needs a long hovering time; the engine is required to have high fuel economy, but the jet engine cannot meet this requirement.…”
Section: Introductionmentioning
confidence: 99%